Talented students in the new inclusive schools (Journal of Parents and Teachers, 2014)
Some students suffer a lot in their classrooms, and do so in silence. They feel that their skills are not "normal" because they do not meet the standards that are considered appropriate to the particular course, age, etc. to the curricular level . Then, they  try to hide their talent, and, very often, the lack of a tutor / teacher who can evaluate and redirect these circumstances can cause irreparable damage, which  can lead students to academic failure or immerse students in some psychological conditions of suffering, insecurity, isolation ... "(By Enric Roca)
Keywords: Talent; giftedness; potentiality; creativity; motivation; connectivity; insights; cooperative work; dyssynchrony; self-regulated learning; education; educational orientation